Central Bank Collateral Frameworks : Principles and Policies - McCaughrin, Rebecca; Chailloux, Alexandre; Gray, Simon (Washington, D.C. : International Monetary Fund, 2008)
Central bank collateral policies came under pressure with the 2007-08 financial market crisis. This paper addresses the rationale for and constraints in taking collateral, and recent practices in different collateral frameworks. It then considers the risks of adverse selection. The paper concludes that (i) the collateral framework needs to include market incentives; (ii) central banks face trade-offs between risk and counterparty access; (iii) emerging markets may see pressure on collateral policies in coming years; and (iv) further work is required to develop pricing incentives and the structure of central bank facilities, both during normal times and in periods of market stress.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet